Indigenous communities’ responses to the COVID-19 pandemic and consequences for maternal and neonatal health in remote Peruvian Amazon: a qualitative study based on routine programme supervision - Luis Huicho; Stefan Reinders; Angela Alva; Magaly M Blas (BMJ Open)
Aim To explore indigenous communities’ responses to the COVID-19 pandemic and its consequences for maternal and neonatal health (MNH) care in the Peruvian Amazon.Methods Mamás del Río is a community-based, MNH programme with comprehensive supervision covering monthly meetings with community health workers (CHW), community leaders and health facilities. With the onset of the lockdown, supervisors made telephone calls to discuss measures against COVID-19, governmental support, CHW activities in communities and provision of MNH care and COVID-19 preparedness at facilities. As part of the programme’s ongoing mixed methods evaluation, we analysed written summaries of supervisor calls collected during the first 2 months of Peru’s lockdown.Results Between March and May 2020, supervisors held two rounds of calls with CHWs and leaders of 68 communities and staff from 17 facilities. Most communities banned entry of foreigners, but about half tolerated residents travelling to regional towns for trade and social support. While social events were forbidden, strict home isolation was only practised in a third of communities as conflicting with daily routine. By the end of April, first clusters of suspected cases were reported in communities. COVID-19 test kits, training and medical face masks were not available in most rural facilities. Six out of seven facilities suspended routine antenatal and postnatal consultations while two-thirds of CHWs resumed home visits to pregnant women and newborns.Conclusions Home isolation was hardly feasible in the rural Amazon context and community isolation was undermined by lack of external supplies and social support. With sustained community transmission, promotion of basic hygiene and mask use becomes essential. To avoid devastating effects on MNH, routine services at facilities need to be urgently re-established alongside COVID-19 preparedness plans. Community-based MNH programmes could offset detrimental indirect effects of the pandemic and provide an opportunity for local COVID-19 prevention and containment.